ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN DAYA TARIK IKLAN TERHADAP MINAT BELI SEPEDA MOTOR YAMAHA (Studi kasus pada konsumen Yamaha SS Cabang Kedungmundu Semarang) - Faikar Annafik, Aldaan; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2012)
Yamaha is one of the largest automotive company in Indonesia. In particular, this study reviews how Yamaha attempt to increase sell their product in market that is currently dominated by Honda. This research was based a decrease in sales of Yamaha motorcycles in the period 2010-2011and decrease in sales of Yamaha motorcycles in Yamaha SS Cabang Kedungmundu Semarang in August-December 2011. This sales decline shows a decrease in consumer buying interest on Yamaha motorcycle products. This research is purpose to find out whether the quality of product, price, and advertising appeal affect on consumer willingness to buy in Yamaha motorcycle products and analyzing the most dominant factor influencing consumer’s buying interest on Yamaha motorcycle in Yamaha SS Cabang Kedungundu Semarang. This research it used 100 samples that was taken from to 100 consumer Yamaha SS Cabang Kedungmundu Semarang obtained by using accidental sampling techniques. Then conducted an analysis of data obtained in the form of quantitative and qualitative analysis. Quantitative analysis involves the validity and reliability testing, test classic assumptions, multiple regression analysis, Goodness of Fit test through regression coefficient (R2), F test and t test. Qualitative analysis is an interpretation of the data obtained in this study and the results of data processing is carried out by giving a description and explanation. The data that have met the test of validity, reliability, and test the assumptions of classical processed to produce a regression equation as follows: Y = 0,388 X1 + 0,364 X2 + 0,205 X3 Order individually from each of the most influential variable is the variable product quality with regression coefficient of 0.388, then price variable with regression coefficient of 0.364. While the variables that affect the lowest advertising appeal with regression coefficient of 0.205. The model equation has a calculated F value of 32.871 and a significance level of 0,000. Where F count is greater than F table (3.09) and with a smaller significance level of α (0.05). It shows that the independent variables in this research is jointly influential to the dependent variable is willingness to buy.